Sex Differences in Dementia Primary Care Performance and Health Service Use: A Population‐Based Study. Issue 5 (5th February 2020) - Sourial, Nadia; Vedel, Isabelle; Godard‐Sebillotte, Claire; Etches, Jacob; Arsenault‐Lapierre, Genevieve; Bronskill, Susan E.
Abstract : OBJECTIVES: Growing evidence points to underlying sex differences in the risk factors and clinical presentation of dementia. It is unclear, however, whether sex differences also exist in the management and healthcare utilization of persons with dementia. We compared primary care performance and health service use indicators for newly identified men and women with dementia in Ontario, Canada, over a 12‐year period. DESIGN: Population‐based, repeated cohort study between 2002 and 2014. SETTING: Ontario, Canada. PARTICIPANTS: A total of 318 350 community‐dwelling adults, aged 65 years and older, newly identified with dementia, followed for up to 1 year. MEASUREMENTS: Eighteen indicators of primary care performance and health service use were assessed. RESULTS: Approximately 60% of the study population were women. Few differences in the indicators were observed between sexes, although men had fewer diagnoses first recorded by the family physician, more visits to noncognition specialists, less use of home care, more hospitalizations and readmissions, and longer discharge delays. Most indicators remained relatively stable over time for both men (median relative change = 13.7%; interquartile range [IQR] = 4.5%‐29.7%) and women (median relative change = 15.7%; IQR = 5.9%‐31.5%). Notable improvements over time for both sexes included access to an interprofessional primary care team, use of home care, and decreased use of long‐term care. Areas of worsening included a higher occurrence of emergency department visits, lower continuity of care, and longer discharge delays. CONCLUSION: These findings raise awareness on the similarities and differences in management and health system use for men and women newly diagnosed with dementia, particularly the imbalance in hospital and home care use. As health systems continue to adapt to meet the needs of the growing dementia population, policy makers and clinicians should be mindful to develop care plans and interventions that consider the influence of sex on the need for services. J Am Geriatr Soc 68:1056–1063, 2020